Basic coagulation tests as surrogates of dabigatran levels in a pre-operative setting: Analysis of five activated partial thromboplastin time reagents and thrombin time. Issue 171 (November 2018) - Dubé, Catherine; Douketis, James D.; Moffat, Karen A.; Schulman, Sam; Blais, Normand
Abstract: Background: In patients who are receiving dabigatran, a direct oral anticoagulant, measuring the anticoagulant effect before surgery may be needed in certain circumstances. Although the dilute thrombin time (dTT) can reliably measure dabigatran levels, it is not consistently available. More commonly used coagulation tests, including the activated partial thromboplastin time (aPTT) and thrombin time (TT) might have clinical utility but their accuracy is uncertain. Methods: 103 patients stopped dabigatran 1–4 days before an elective surgery/procedure as part of a standardized dabigatran interruption protocol. With a blood sample taken just before surgery, we assessed the accuracy of five aPTT assays (Actin FS, Stago PTT, C.K. PREST, HemosIL aPTT-SP, SynthASil) and TT to measure the residual anticoagulant effect of dabigatran. We determined the sensitivity, specificity and other accuracy indices of these assays to predict a dabigatran level > 30 ng/mL as determined by a reference standard test, the dTT (Hemoclot). Results: Of five aPTT reagents, four assays had excellent (100%) and one assay had good (93%) sensitivity to detect a level of dabigatran > 30 ng/mL, but all had insufficient specificity (50–74%). A TT > 90 s had good sensitivity (93%) and excellent specificity (100%). Conclusion: Five aPTT assays had good sensitivity but poor specificity to detect low levels of dabigatran (≤30 ng/mL) after standardized dabigatran interruption before an elective surgery/procedure, thereby limiting the use of aPTT as an alternative to the dTT in preoperative settings. Highlights: A normal aPTT result from five reagents indicated a low concentration of dabigatran in a pre-operative setting. There was inter-reagent variability in specificity limiting overall accuracy. As performed by our centers, a thrombin time result ≤ 90 s was well correlated with a dabigatran level of ≤30 ng/mL.